A green extraction method for gelatin and its molecular mechanism. (March 2022) - Feng, Xin; Liu, Tingwei; Ma, Liang; Dai, Hongjie; Fu, Yu; Yu, Yong; Zhu, Hankun; Wang, Hongxia; Tan, Hongxia; Zhang, Yuhao
Abstract: In this work, a green extraction method of gelatin was proposed to replace traditional acid and alkali treatment by microwave-rapid freezing-thawing coupling method. The mechanism of rapid gelatinization of fish skin collagen induced by microwave-rapid freezing-thawing coupling was examined systematically. The results showed that the dense structure of fish skin collagen fibers became loose, the collagen molecular on the surface was gelatinized and degraded gradually, then more internal collagen molecular without gelatinization were exposed with the increase of microwave pre-treatment time (0–60 min), resulting in an increase of gelatin yield (5.32%–19.94%) and a decrease of the gel strength (675.17–419.6 g). With the increase of freezing-thawing cycles (0–3), the gelatinized collagen fibers structure was further loosened and the balance of hydrogen bond was destroyed seriously due to the rapid formation and melting of ice crystals, thus leading to the dissolution and degradation of subunit components. This also resulted in an increases of gelatin yield (13.91%–19.01%) and a decrease of gel strength (580.01–413.33 g). Ultimately, the gelatin yield and gel strength were 17.01% and 591.50 g respectively under optimal conditions (microwave pre-treatment 15 min, one freezing-thawing cycle). This study could provide theoretical basis and guiding significance for the production of gelatin in a green way. Graphical abstract: Image 1 Highlights: A new method of gelatin preparation without using acid and alkali. Gelatinization induced by microwave-rapid freezing-thawing coupling. The covalent bonds could be destroyed by microwave pre-treatment in 15 min. Freezing-thawing mainly destroyed the balance of hydrogen bond between collagen.